Rapid and Environmentally‐Friendly Synthesis of Thiazolidinone Analogues in Deep Eutectic Solvent Complemented with Computational Studies - Gobind Kumar; Pule Seboletswe; Nontobeko Gcabashe; Sanjeev Dhawan; Neha Manhas; Gaurav Bhargava; Rupesh Kumar; Parvesh Singh (ChemistryOpen)
Abstract A greener, safer, and more efficient methodology for the synthesis of (Z)‐5‐benzylidene‐2‐thioxothiazolidin‐4‐ones (3 a–u) and (Z)‐5‐benzylidenethiazolidine‐2,4‐diones (4 a–i) has been developed. The deep eutectic solvent (DES) ZnCl2/urea used as a greener solvent as well as a catalyst in this study accelerated the condensation of rhodanine and thiazolidine‐2,4‐dione with different aldehydes to afford the target scaffolds in excellent yields (88‐98 %). The reaction methodology adopted offered significant advantages such as mild reaction conditions, functional group tolerance, quick reaction time, column‐free isolation, catalytic recyclability, and applicability to gram‐scale production. Moreover, density function theory calculations were carried out to investigate the global reactivity and stability profiles of these compounds. Finally, the green metrics analysis supported the greener nature of the present methodology.